THE THEME OF MOTHERLAND IN ROBERT BURNS POETRY - Aktamova Zarnigor Yahyo qizi; Xalilova Mohinurbonu Jalolovna; Xalmuratova Fariza Elmurad qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article provides a brief summary of the information learned about the poems of Robert Burns and his creative lines of love, with special emphasis on the feelings of love for the motherland and separation from the motherland in his poems.